PENGEMBANGAN SISTEM INFORMASI AKUNTANSI DI YAYASAN GELORA MADANI BATAM - Fendi Hidayat (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2020)
The Gelora Madani Batam Foundation (YGMB) is a non-governmental organization engaged in social, religious and educational fields. In its implementation, YGMB experienced problems in managing financial reports. Therefore, this research will develop an Accounting Information System (SIA) to solve the problems faced by YGMB. In this study using qualitative methods and systems development systems using the waterfall method. SIA is developed based on web using codeigniter framework